Lower 30 Minute Serum Insulin in Healthy Sprague‐Dawley Rats Consuming Chips from Specific Barley Flour Blends. Issue 5 (2nd October 2013) - Harding, Scott V.; Storsley, Joanne; Thandapilly, Sijo J.; Ames, Nancy P.
ABSTRACT: Consumption of whole grains such as barley is known to inversely correlate with insulin resistance, type 2 diabetes, and other chronic diseases. However, data from randomized controlled trials in humans have not produced consistent results. Compositional differences between foods produced from different whole grains are likely to be a main reason for these discrepancies. The purpose of this study was to determine if varying barley flour composition achieved through milling influenced the postprandial glucose and insulin response. Specifically, this study aimed to test barley foods in the form of chips with very low hydration, thereby mimicking human snack foods. Fasted rats ( N = 39) were randomized to one of four barley treatments, all produced from a single variety, Hordeum vulgare L. 'CDC Fibar.' The treatments used were straight‐grade flour (SGF), whole grain flour (WGF), bran flour with high β‐glucan (BF‐BG), bran flour with high insoluble dietary fiber, and wheat flour (WF) as the control. Blood was sampled over 120 min following treatment consumption to measure postprandial glucose and insulin concentrations. Our data showed that although there were no substantial glycemic or insulin effects following one‐time consumption of barley tortilla chips with specific compositions, those rats consuming WGF, SGF, or BF‐BG tended to have lower 30 min serum insulin concentrations compared with those rats consuming WF.